Review on phytochemical constituents of the genus Trichilia and biological activities - SuRilige, SuRilige; Baldoo, Lagshmaa; Lkhagvasuren, Naranbat; AQilatu, AQilatu; Namsrai, Oyuntsetseg (Trends in Immunotherapy, 2024)
The Mongolian nomadic nation has created bone healing, or fracture healing, which is suitable for the extreme weather and territory, unique living conditions, and physical characteristics while struggling to fight diseases during a long historical period. Gradually, this treatment method has gradually developed into a more comprehensive theoretical system throughout history and has unique names due to the thinking scope of the Mongols, their cognition development, and thus their use of it in their everyday lives and continuing to enrich their knowledge. Mongols have rich experience healing bone fractures and injuries from ancient times. They are usually used to perform bone setting and massage therapy. On the other hand, they have experience using herbal and mineral medicines to heal bone fractures and injuries. During their practice, the knowledge of herbal and mineral medicines used for bone fractures and injuries became expansive. After Buddhism reemerged in the 16th century, Mongolian doctors and knowledgeable people wrote many medical books in Tibetan. One of the major representatives was Jambaldorj, who wrote Mongolian materia medica, called “The beautiful wondrous eye ornament,” based on “Four medical tantras.” In treating bone fracture and injury in traditional medicine, firstly, the four treatment methods mentioned in “Four medical tantras” are the main principles and methods, which are wind, bile and phlegm theory, dietary recommendations, advice on behavior, prescribing medicine, and accessory therapy. We concluded that the names of herbal and mineral medicines used to practice bone setting are the same, even though they are mentioned in various sources.